Relationship between the flagellates and the ciliates. - Lee, R E (1992)
The flagellates and the ciliates have long been considered to be closely related because of their unicellular nature and the similarity in the structures of the axoneme of the flagella and cilia in both groups. Most protozoologists believe that the ciliates arose from a flagellate. The flagellates that are most similar in structure to the ciliates are the dinoflagellates and two genera of uncertain taxonomic position, Colponema and Katablepharis. Structurally, dinoflagellates have a number of similarities with ciliates. These include the similarity of the cortical alveoli in the ciliates to the thecal vesicles in the dinoflagellates, the possession of tubular cristae, the similarity of the parasomal sac of the ciliates to the pusule of the dinoflagellates, the possession of similar trichocysts and mucocysts, and some similarity in the feeding apparatus. Colponema spp. are probably related to the dinoflagellates and have many of the same similarities with the ciliates. Katablepharis spp. are very similar in structure to the swarmer (embryo) of the suctorian ciliates. Indeed, reduction in the number of cilia to two in the suctorian swarmer and elimination of the macronucleus would result in a cell that is very similar to the Katablepharis cell. The feeding apparatus of Katablepharis spp. and the rest of the ciliates consists of two concentric microtubular arrays associated with vesicles. Information available from nucleotide sequencing of rRNA places the dinoflagellates in an ancestral position to the ciliates. The rRNA of Colponema and Katablepharis spp. has not yet been investigated. The use of stop codons in mRNA is discussed in relation to phylogeny.